A Study about a Amazonian Meteoritic Specimen by Analytical Techniques - Cerón Loayza, María L. (2017)
Herein, it is introduced the analysis of a meteoritic specimen discovered in the Peruvian Amazonia. According to the analysis by dierent physical techniques carried onto a fragment of it, this meteorite belongs to the ordinary chondrites. Specifically, we have used transmission Mössbauer spectroscopy and energy dispersive X-ray fluorescence.The results with these techniques show that the samples have relatively large amounts of Si, Al and Fe. Likewise, since transmission Mössbauer spectroscopy is an isotopically more selective technique, we have observed the presence of magnetic sites assigned to the taenite (Fe,Ni) and troilite (Fe,S) phases. We also realized the presence of three paramagnetic doublets assigned to Fe2+: one associated with olivine (Fe,Mg)2SiO4;other, to pyroxene (Fe,Mg)SiO3; and third doublet, to one Fe3+ site.